Uterine leiomyoma research - Tae Hee Kim; Hae Hyeog Lee (Kosin Medical Journal, 2015)
Abstract Uterine leiomyoma is the most common type of benign tumor in women of reproductive age. This disease is rare before menarche, and its incidence decreases after menopause. Uterine leiomyoma is known to be related to hormonal changes, but the precise underlying mechanism has yet to be determined. Although it is a benign disease, the most common form of management involves surgical intervention. Uterine leiomyoma is also related to infertility and obstetric complications. Here, we present a review of the literature regarding uterine leiomyoma and discuss management of this disease.